Clonagem e expressão da lectina Frutapina em Escherichia coli: análises estruturais - Sousa, Felipe Domingos de (2018)
Plant lectins are proteins which are able to promote specific recognition and reversible binding to selective sugars in carbohydrates or glycoconjugates without altering their covalent structure. Due to these inherent features, lectins can interact with cell surface moieties and display both inflammatory and anti-inflammatory, as well as immunomodulatory and immunostimulatory, properties. Artocarpus incisa is a widespread plant, common in pan-tropical regions, and popularly known as “fruta-pão” (breadfruit) in Brazil, where it is consumed cooked by local populations. Frutapin (FTP) is the second most abundant lectin in A. incisa seeds, belonging to the mannose-binding subfamily of jacalin-related lectins (JRL). FTP proved difficult to purify with very low yields and contamination with Frutalin (a multiple-binding lectin and most abundant in the same species), which have frustrated its characterization so far. In this work, we developed a high-level expression system of biologically active recombinant FTP in Escherichia coli BL21 using a SUMO-tag strategy, optimizing conditions with the best set yielding >40 mg/l culture of soluble active rFTP. Apo-FTP, FTP–mannose and FTP–glucose crystals were obtained, and they diffracted X-rays to a resolution of 1.58 (P212121), 1.70 (P3121) and 1.60 (P3121) Å, respectively. The best solution showed four monomers per asymmetric unit. Molecular dynamics (MD) simulation suggested that FTP displays higher affinity for mannose than glucose. The ability of rFTP to interact with TLR4 was evaluated using HEK-Blue™-hTLR4 cells. Also, the effect of FTP on fibroblast biology was assessed through cell migration assay, IL-6 production and western blot analysis. rFTP did not show cytotoxicity to human skin fibroblasts (<1,000 µg/mL). After 8 h, samples treated with FTP had significant numbers of migrated cells when compared to controls, migrating across the denuded area and effecting efficient wound closure. rFTP was able to potently stimulate the TLR4 pathway in a manner similar to that observed with LPS. High levels of IL6 production were observed when compared to untreated cells (p<0.0001). The levels of pERK 1/2 and MyD88 were significantly higher when compared to untreated cells after 24 h (p<0.05). In conclusion, this study showed that rFTP was non-cytotoxic to human fibroblasts. Given that fibroblasts play an important role in tissue repair, rFTP may represent a potential therapeutic biomolecule for wound healing and other related skin diseases.